. مستوى وعي طلبة الدكتوراه بتدابير الوقاية من السرقة العلمية: دراسة ميدانية بجامعة محمد خضير بسكرة القطب الجامعي شتمة - زميري خولة; ورخ بلقاسم (University Of Eloued جامعة الوادي, 2023)
Scientific plagiarism is considered one of the unethical phenomena widespread in the university milieu, which in turn negatively affects the entire higher education system because of its role in declining the status and reputation of the university and the credibility of its staff of students and professors, and on this basis this paper aims to identify forms of scientific plagiarism In which the doctoral students fall, and the level of their awareness of the mechanisms of protection from scientific plagiarism, and we relied on the descriptive approach in that, and we also used the questionnaire tool to collect data from the study sample. In which doctoral students fall, and that lack of knowledge of the laws of scientific plagiarism is the most common cause. On the other hand, the integration between legal methods and technical methods (software for detecting plagiarism) is the best solution that allows reducing the phenomenon of plagiarism in the university community.
The level of doctoral students’ awareness of measures to prevent scientific plagiarism A field study at Mohamed Kheidar University in Biskra, the university pole of cursing
مداخلة
Keywords: السرقة العلمية; الانتحال العلمي; أخلاقيات البحث العلمي; طلبة الدكتوراه; جامعة بسكرة: الجزائر; scientific theft; plagiarism; scientific research ethics; PhD students; University Biskra: Algeria